ROTOR DYNAMIC DIAGNOSTICS USING FINITE ELEMENT ANALYSIS - Mohd Burhan, Muhammad Izqandar (IRC, 2021)
This dissertation presents a study on the Final Year Project (FYP) titled Rotor Dynamics Diagnostics using Finite Element Analysis.